2006
DOI: 10.1177/0040517506063393
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Automotive Interior Noise with Natural Fiber Nonwoven Floor Covering Systems

Abstract: Eliminating unwanted noise in passenger compartments of vehicles is important to automobile manufacturers. The ability to reduce noise inside the vehicle enhances the perceived value of the vehicle to the consumer, and offers a competitive advantage to the manufacturer. Several methods are presently employed to reduce noise and its sources, one of which uses sound-absorbing materials attached to various components such as floor-coverings, package trays, door panels, headliners and trunk liners. Natural fibers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(65 citation statements)
references
References 3 publications
0
58
0
Order By: Relevance
“…Sound in an object (e.g., a commercial passenger car) is generally propagated through the air (airborne sound), and by vibrations of the body (structural sound). In the science of acoustical control, two classes of acoustical treatments can be used to address airborne noise, namely barriers and absorbers while for structure-borne noise, isolators and dampers are two possible treatments [Parikh et al, 2006]. Natural fibers and their composites are potential sound absorbers and noise reducers.…”
Section: Sound and Vibration Damping Aspects Of Plant Fiber Compositesmentioning
confidence: 99%
“…Sound in an object (e.g., a commercial passenger car) is generally propagated through the air (airborne sound), and by vibrations of the body (structural sound). In the science of acoustical control, two classes of acoustical treatments can be used to address airborne noise, namely barriers and absorbers while for structure-borne noise, isolators and dampers are two possible treatments [Parikh et al, 2006]. Natural fibers and their composites are potential sound absorbers and noise reducers.…”
Section: Sound and Vibration Damping Aspects Of Plant Fiber Compositesmentioning
confidence: 99%
“…The use of kenaf fiber can provide lower density than the traditional materials and has resulted in lightweight and eco-friendly automotive interiors. Not only that, it has been shown that the cellulosic-based non-woven fiber has better sound absorption and noise level reduction (Parikh et al 2006). This sandwich layer composite is a very efficient structural design with the benefit of being lower in cost.…”
Section: Introductionmentioning
confidence: 99%
“…Kenaf, jute, waste cotton as well as flax are mixed with polypropylene and polyester. It is found that their sound insulation performance is good and relatively better than commercial cotton pad [5]. Tascan and Vaughn (2006) study the effect of total surface area and fabric density of a needle punch nonwoven fabric on the acoustical performance.…”
Section: Introductionmentioning
confidence: 99%